2023
DOI: 10.1002/dmrr.3616
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a risk prediction model for the recurrence of foot ulcer in type 2 diabetes in China: A longitudinal cohort study based on a systematic review and meta‐analysis

Abstract: Aims To develop and validate a risk prediction model for Chinese patients with type 2 diabetes with the recurrence of diabetic foot ulcers (DFUs) based on a systematic review and meta‐analysis. Methods A prospective analysis was performed with 1333 participants and followed up for 60 months. Three models were analysed using a derived cohort. The risk factors were screened using meta‐analysis and logistic regression, and the missing variables were interpolated by multiple imputation. The internal validation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Through multiple regression analysis, it was found that the Wagner grading was an independent risk factor for DF amputation, which is consistent with previous research results. 21 , 22 This suggests that as the Wagner grading increases, the risk of amputation increases. Therefore, it is necessary to assess the severity of ulcers as early as possible, in order to adopt scientific and effective treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Through multiple regression analysis, it was found that the Wagner grading was an independent risk factor for DF amputation, which is consistent with previous research results. 21 , 22 This suggests that as the Wagner grading increases, the risk of amputation increases. Therefore, it is necessary to assess the severity of ulcers as early as possible, in order to adopt scientific and effective treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] In recent years, there emerged multiple studies identifying the critical factors contributed to the DFU, which reached to the consensus were listed as: age, gender, duration of DM, previous DFU, location of ulcer, smoking, prior amputation, foot deformity, DPN, PAD, other metabolic factors such as hypertension, lipids, glycated hemoglobin A1C (HbA1C), body mass index (BMI), kidney function and others. [18][19][20] Nonetheless, few clinical investigations identified a comprehensive scenario for patients at risk for DFU, and fail to recognize the systemic factors such as hepatic function, thyroid function, nutrients status, and their relationship with the macro-or micro-vasculopathy.…”
Section: Introductionmentioning
confidence: 99%